Enzymes of agmatine degradation and the control of their synthesis in Klebsiella aerogenes. - Friedrich, B (1979)
The degradation of agmatine to succinate by Klebsiella aerogenes occurs in five steps. The enzyme catalyzing the first step, agmatinase, is induced by agmatine. The enzymes catalyzing the second and third steps, putrescine aminotransferase and 4-aminobutyraldehyde dehydrogenase, are induced by putrescine and also by their product, 4-aminobutyrate. The enzymes catalyzing the fourth and fifth steps, 4-aminobutyrate aminotransferase and succinate semialdehyde dehydrogenase, are induced by 4-aminobutyrate. This compound also serves as gratuitous inducer of the catabolic acetylornithine aminotransferase. The formation of the enzymes responsible for agmatine degradation is regulated not only by induction, but also by catabolite repression and activation by glutamine synthetase.